Building resilience : developing a resilience toolkit for employability in built environment graduates : final report. - Davis, Peter; Sher, Willy; McLaughlin, Patricia; Chester, Andrea; Mills, Anthony (Australia. Dept of Education, Skills and Employment, 2020)
This seed project focuses on the Office of Learning and Teaching priority of employability skills. The aim of the project, funded throughout 2016, is to develop an online toolkit of case studies and practical resilience problem-solving exercises for use by built environment academics and designed to help undergraduate students cope. The project was founded on the premise that on graduation from university to workplaces many students lose access to support structures such as peers, academic mentoring, time management advice, environmental familiarity and organisational understanding. This may lead to tension, stress and failure to perform effectively in new workplaces, especially if the workplace itself is stressful. Not knowing who to ask or what question should be asked, or failing this, where to look for answers, becomes an insurmountable problem and exacerbates high levels of anxiety. It is suggested that the ability to cope and draw on resilience skills may provide answers for graduates. At the outset, there was a suggestion that the development of resilience skills is not included as learning outcomes within courses, units of study or programs of learning within the built environment discipline. The project had three objectives that were all completed. In completing an audit of built environment programs in Australia we identified the extent and quality of resilience training. The major output was to develop an online resilience toolkit designed to showcase example case studies and practical resilience problem-solving exercises for use by built environment academics in Australia. Finally, we disseminated our research and the final resilience toolkit through academic journals, industry engagement, final report and presentations at the Australasian University Building Educators Association (AUBEAU) 2016 and 2017. [Publisher summary, ed]